Baixios de viaduto: novos olhares - Camañes Guillén, Maria Isabel (2021)
This research consists in acknowledging the growth of the city through viaducts and bridges, transposing the natural barriers imposed by the territory of the city of São Paulo, as well as analyzing the resulting spaces under these structures, here cal led Underpass Viaducts, recognizing the processes of development and management of initiatives and the interferences generated in the region where road structures were inserted. The city of São Paulo grew, many roads were changed, but the different levels of the city needed to be overcome, resulting in urban interventions responsible for the emergence of viaducts. São Paulo, known as the city of viaducts, currently counts 184 viaducts and bridges, of which 145 are viaducts. The question regar ding the occupation of these residual spaces, under the viaducts of the city of São Paulo arises from the finding that the neighborhoods located in their surroundings, when they receive the infrastructure, after, their meshes are consolidated, develop a process of deterioration. In these places, activities not sanctioned by the public authorities are usually carried out, in addition to providing shelter for a homeless population. This social reality, experienced by large Brazilian cities contributes to the emergence of derelict places, inhibitors of the flow and permanence of the inhabitants of the city. The context in which the thesis is included brings a difficult reality, both for understanding and approaching. This characteristic of the viaduct shallows of São Paulo is very different from those found in European cities. The projects developed for these cities are far different from those implemented in our country. In this inves tigation we seek to understand the possibilities of urbanity in these spaces, unders tanding how successful initiatives are managed, as well as the existing dynamics in the processes. As objective, we try to highlight the potentiality of occupation of these shallows and, from it, recognize this urbanity, through the identification of the main attributes of quality. The analysis should reveal from the attributes, the main urban elements responsible for qualifying these spaces, developing a foundation for the formulation of projects and public policies to contribute to the integration of the highways to the rest of the city. The research was split in three parts, in the first are the methodological procedures used, such as the study of the urban morphology of the city of São Paulo, evaluation of the urbanity of viaduct depths, perception of the population about these areas through a questionnaire, recognition of the potentialities of viaduct shallows, with evaluation of strengths and weaknesses, opportunities and threats, and testimonies of actors who already develop activities in these spaces. In the second part of the research, we have the theoretical processes, with a global approach on urban mobility infras tructures and cases of areas of the referential viaduct shallows, illustrating the most frequent urbanity attributes in these locations and the strategies used to reach them. In the third and final part, there are the case studies, with a sampling of all the viaducts of São Paulo, to recognize the potentialities and the best initiatives for the management of these spaces, exposing strategies of the public authorities and local actors.